Customer perceptions and behaviors of eating and buying street food in Terengganu, Malaysia / Nurul Abieyatina Amran and Nur Atiqah Shuhada Omar - Amran, Nurul Abieyatina; Omar, Nur Atiqah Shuhada (2021)
Eating out is part of the culture in Malaysia. Street food, in particular, has been popular not only among the locals but also the international tourists. Due to its popularity and affordable, there are many people loves to eat street food compared to other foodservice restaurant especially local people and tourist who loves to eat street food at Terengganu. Understanding the level satisfaction of street food among customer is very important. An extended analysis of previous research revealed that there was a small range of past surveys that discuss customer satisfaction by taking into consideration both the level of service and the quality of food. The purpose of this study is to identify the factors that influence customer satisfaction in eating and buying street food and to evaluate the level of their satisfaction towards street food at Terengganu, Malaysia. The customer in this study is referring to local people and tourist who buy and eat street food at Terengganu. A convenience sampling is used and the total respondent in this study are 273 people. The data were analyzed using SPSS and the result reveal customers had a good perception of street food in terms of cleanliness, food quality, food safety, service quality and pricing. The finding shows that all of the factors had significant positive effect on overall customer satisfaction. This study is useful for individuals who are interested to start a street food business as well as to help those who are already in the business better understand their customer.